2009
DOI: 10.1002/xrs.1172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aerosol particle sources in semi‐rural area of Kwabenya, near Accra, Ghana, by EDXRF techniques

Abstract: Small aerosol particles have for a long time been known to be harmful to humans, and are today regarded to cause a larger number of deaths than traffic accidents globally. Energy dispersive x-ray fluorescence (EDXRF) is a well known method that has been used for identification of toxic as well as non-toxic elements in the particles. The combination of elements will together with other information help to identify the sources and predict the effects of particles on environment and human health.The present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
6
16
6
Order By: Relevance
“…The average PM 2.5 obtained for the sampling period was 32.4 mg/m 3 , which is higher than the World Health Organization (WHO) annual mean value of 10 mg/ m 3 and 24-hr mean of 25 mg/m 3 . The results of the species concentrations in this work compare well with other works in Ghana and Egypt (Table 2) (Ofosu et al, 2012;Aboh et al, 2009;Abu-Allaban et al, 2002).…”
Section: Resultssupporting
confidence: 85%
“…The average PM 2.5 obtained for the sampling period was 32.4 mg/m 3 , which is higher than the World Health Organization (WHO) annual mean value of 10 mg/ m 3 and 24-hr mean of 25 mg/m 3 . The results of the species concentrations in this work compare well with other works in Ghana and Egypt (Table 2) (Ofosu et al, 2012;Aboh et al, 2009;Abu-Allaban et al, 2002).…”
Section: Resultssupporting
confidence: 85%
“…[28] All material presented in this study indicates that long transported Harmattan dust do not deposit in southern Ghana when the ITD is positioned in its yearly average southernmost position around 5 N, contrary to what is concluded by, e.g., Aboh et al [2009] and Dionisio et al [2010]. Additionally the current results imply that the interpretation of the higher dust mass concentrations in the Harmattan season as reported by Afeti and Resch [2000] and Sunnu et al [2008] may be caused by dry convection rather than being long transported Harmattan dust.…”
Section: Discussioncontrasting
confidence: 77%
“…All material presented in this study indicates that long transported Harmattan dust do not deposit in southern Ghana when the ITD is positioned in its yearly average southernmost position around 5°N, contrary to what is concluded by, e.g., Aboh et al . [] and Dionisio et al . [].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 aimed to compare PM 10 total and element concentrations measured in Cape Verde with the concentrations measured in other sites of the globe. Results showed that PM 10 concentrations in Cape Verde were higher than concentrations measured in Europe and America, but lower than the concentrations measured in a suburban area in Ghana (Aboh et al, 2009); in Agra (India), which is bounded by the Thar Desert of Rajasthan (Kulshrestha et al, 2009); and in Hangzhou, an industrialized and urbanized region (Cao et al, 2009). A similar behavior was found for Fe.…”
Section: Pm 10 Element Characterizationsupporting
confidence: 79%
“…Potassium concentrations were higher in Cape Verde compared with concentrations measured in Europe and America but lower than concentrations measured in Pakistan, Ghana, and China (von Schneidemesser et al, 2010;Aboh et al, 2009;Cao et al, 2009). Almeida and coworkers (2006b) indicated this element is associated with soil (insoluble coarse fraction), 244 M. ALMEIDA-SILVA ET AL.…”
Section: Pm 10 Element Characterizationmentioning
confidence: 82%